Peran Ayah dalam Al-Qur’an dan Implikasinya terhadap Kehidupan Anak: Pendekatan Tafsir Maudhu‘I - Shofiya fikri handayani; Septiawadi Septiawadi; Siti Badiah; Andien putri olivia Arivin; Didin Toharudin; Wahyu Ramdan Tri Handoko (Institut Nalanda, 2026)
The phenomenon of fatherlessness and the weakening of fathers' involvement in the family has become a social problem that impacts the emotional, moral, and social development of children. In modern society, the role of fathers is often understood only as breadwinners, whereas the Qur'an provides a broader picture of fathers' responsibilities in the education, communication, protection, and social development of children. Studies on the role of fathers in the Qur'an are also still relatively limited, especially those using the maudhu'i interpretation approach. Therefore, this study focuses on the concept of the role of fathers in the Qur'an and its implications for the development of children's lives. This study uses a qualitative approach with a library research type. Data were obtained from Qur'anic verses about the role of fathers, classical and contemporary interpretation books, and other supporting literature. The analysis was conducted using the maudhu'i interpretation method by collecting verses related to the theme and then analyzing them descriptively and analytically. The results show that the concept of the father's role in the Qur'an encompasses the responsibility of caring for the family, educating children with the values ​​of monotheism and morality, establishing wise communication, and fostering children's social life through role models and affection. The implications of this role are seen in the formation of religious character, emotional stability, social skills, a sense of responsibility, and moral resilience in children in facing the challenges of modern life.